2011
DOI: 10.2478/v10214-011-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potentials of polyphenolic extracts from leaves of trees and fruit bushes

Abstract: Antioxidant potentials of polyphenolic extracts from leaves of trees and fruit bushesThe aim of the work was to determine the antioxidant potential of extracts from leaves of strawberry, blackcurrant and apple in relation to lipids contained in the erythrocyte membrane. The studies performed have shown that the substances used protect membrane lipids against oxidation, clearly reducing the level of free radicals in erythrocyte ghosts suspension. The antioxidant activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…The percent content of polyphenols in the extracts was determined with the liquid chromatography (HPLC) method described by Oszmiański et al [19]. Phenolic compounds were identified with the HPLC/DAD method described by Oszmiański et al [20] and the method of UPLC/ESI/MS analysis described by Cyboran et al [3]. Polyphenols were isolated from leaves by extraction with water containing 200 ppm of SO 2 , the ratio of solvent to leaves being 3:1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The percent content of polyphenols in the extracts was determined with the liquid chromatography (HPLC) method described by Oszmiański et al [19]. Phenolic compounds were identified with the HPLC/DAD method described by Oszmiański et al [20] and the method of UPLC/ESI/MS analysis described by Cyboran et al [3]. Polyphenols were isolated from leaves by extraction with water containing 200 ppm of SO 2 , the ratio of solvent to leaves being 3:1.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the protection of biological membranes, which are the main site of attack by free radicals, is directly due to the presence of polyphenols in the membrane and indirectly due to scavenging of free radicals in the medium. It has been shown that extracts from leaves of strawberry, blackcurrant and apple have very good antioxidant properties with respect to biological membranes, the strawberry extract exhibiting the highest activity, comparable to that of Trolox ® [3]. Plant extracts as substances of high biological activity have long been used in prevention and treatment, though the mechanism of their action at the cell and molecular level is not yet fully explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological properties of CGA are primarily attributed to its capacity to donate hydrogen atoms of the phenolic ring to free radicals, thus inhibiting oxidation process [7]. Research confirms that CGA, among the polyphenol compounds that occur in plants, is an important natural antioxidant [5,6,[8][9][10][11][12]. The polyphenols are scavengers of free radicals which are responsible for oxidizing biological structures, with resultant damage and pathological states of an organism.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorogenic acid (CGA) is a phenolic compound found in various parts of the plant, in fruits, vegetables, and herbs. It is present in large quantities in coffee beans, dry plums, cocoa fruits, hawthorn, nettle, bilberries, sunflower seeds, honeysuckle, potato tubers, and apples [1][2][3][4][5][6]. The biological properties of CGA are primarily attributed to its capacity to donate hydrogen atoms of the phenolic ring to free radicals, thus inhibiting oxidation process [7].…”
Section: Introductionmentioning
confidence: 99%